THE CLINICAL CHARACTERISTICS AND SURGICAL OUTCOMES OF CONGENITAL CATARACT TREATMENT AT THE VIETNAM NATIONAL EYE HOSPITAL DURING THE PERIOD 2024-2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical characteristics and surgical outcomes of congenital cataract treatment at the Vietnam National Eye Hospital during the period 2024-2025.Subjects and methods: This was a prospective interventional case series conducted on 15 eyes (10 patients) diagnosed with congenital cataract who underwent cataract extraction and intraocular lens implantation. All patients were examined preoperatively and followed up for 3 months postoperatively.Results: The patients’ ages ranged from 5 months to 15 years, with a mean age at surgery of 6.44 ± 4.11 years. The most common presenting symptoms were poor vision, strabismus, and leukocoria. The predominant types of cataract were nuclear (46.67%) and capsular (40%). All patients underwent cataract extraction with intraocular lens implantation. The mean visual acuity improved from 0.88 ± 0.42 LogMAR preoperatively to 0.27 ± 0.15 LogMAR at 3 months postoperatively. The main residual refractive error after surgery was hyperopia. Postoperative complications included elevated intraocular pressure in 1/15 eyes and uveal inflammatory reaction in 1/15 eyes.Conclusion: Surgical treatment of congenital cataract significantly improves postoperative visual acuity. Careful postoperative monitoring is necessary to detect and manage possible complications.
Keywords: Congenital cataract, surgery, surgical outcomes